2001
DOI: 10.1016/s0925-4773(01)00465-8
|View full text |Cite
|
Sign up to set email alerts
|

Foxn4 – a new member of the forkhead gene family is expressed in the retina

Abstract: We report the cloning and expression of a novel murine forkhead/winged helix family member--Foxn4--that is expressed during neural development in the retina, the ventral hindbrain and spinal cord and dorsal midbrain. Retinal Foxn4 expression is associated with the zone of proliferating progenitor cells. In the mouse mutant ocular retardation (or(J)), Foxn4 expression in the retina is significantly reduced and terminates prematurely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 15 publications
3
33
0
Order By: Relevance
“…It is also expressed in the developing spinal cord but a role has yet to be assigned during spinal neurogenesis (29). We show here that Foxn4 is expressed in a subset of p2 progenitors that coexpress Mash1.…”
mentioning
confidence: 70%
“…It is also expressed in the developing spinal cord but a role has yet to be assigned during spinal neurogenesis (29). We show here that Foxn4 is expressed in a subset of p2 progenitors that coexpress Mash1.…”
mentioning
confidence: 70%
“…It was found to be downregulated in oral squamous cell carcinoma (OSCC) (Chang et al, 2005). Foxn4 is expressed in the retina (Gouge et al, 2001). A knockout analysis in mice revealed that Foxn4 is involved in the development of amacrine and horizontal cells during retinogenesis.…”
Section: Abstract: X Laevis Foxn Transcription Factor Eye Anlagementioning
confidence: 99%
“…6 shows the expression of the Xenopus FoxN4 gene. Similar to the mouse orthologue (Gouge et al, 2001), FoxN4 transcripts are predominantly localised in the developing eye. A weak staining is observed in the eye anlage at stage 18 (Fig.…”
mentioning
confidence: 98%
“…Compared with other fox TF subfamilies, the foxN subfamily members were discovered more recently. In mammals, the foxN subfamily has six members: foxN1 (Nehls et al, 1994), foxN2 (human T-cell leukemia virus enhancer factor, HTLF) (Li et al, 1992), foxN3 (checkpoint suppressor, CHES1) (Pati et al, 1997;Scott and Plon, 2003), foxN4 (Gouge et al, 2001), foxN5 (foxR1) (Katoh, 2004a) and foxN6 (foxR2) (Katoh, 2004b). foxN1 is widely known because a foxN1 mutation produces the immune-deficient nude mice.…”
Section: Introductionmentioning
confidence: 99%